OBSTACLES IN IMPLEMENTING THE RADEC LEARNING MODEL AS A FORM OF DEVELOPING STUDENTS' SOCIAL INTERACTION ABILITIES OF MI TEACHER EDUCATION STUDENTS - Nasyariah Siregar Siregar; Fia Alifah Putri; Wahyu Iskandar (STAI Ma'had Aly Al-Hikam Malang, 2026)
Study This focus attention to the identification of Obstacles in Implementing the RADEC Learning Model as an Effort to Develop Ability Interaction Social Student. Research This use approach combination or mixed methods for analyze application of the RADEC (Reading, Answering, Discussing, Evaluating, and Creating) learning model in development ability interaction social student. With using the Concurrent Embedded model, and using the purposive sampling technique. With results study This are the Obstacles in Implementing the RADEC Learning Model as Form Development Ability Interaction Social Students (1) Variations Ability Reading and Initial Comprehension of Students. Stage First in RADEC is Read, which requires student understand material in a way independent before lectures. However, the ability literacy and level understanding beginning PGMI students still diverse. As a result, the Answer and Discuss process becomes not enough effective Because student No own foundation knowledge that should be obtained at the stage beginning (2) Low Courage and Skill Communication in Discussion. The RADEC model demands student active discuss, explain, and put forward ideas in front of Friend peers. Common obstacles appear is Lots PGMI students who are still not enough believe self, passive, or Afraid put forward opinion. Culture academics who have not fully support openness and courage speak make the Discuss and Explain stages are not running optimally. As a result, the goal RADEC main for increase interaction social and collaboration become hampered. (3) Limitations Time Management. limitations time face advance make a number of RADEC stages impressed rush, especially at the Explain and Create stages which require time more Lots For exploration and collaboration.